Different contribution of HLA-DR and -DQ genes in susceptibility and resistance to insulin-dependent diabetes mellitus (IDDM) - Yasunaga, S; Kimura, A; Hamaguchi, K; Ronningen, K S; Sasazuki, T (Tissue antigens, 1996)
Previous studies have indicated that certain alleles of HLA-DR and -DQ genes were strongly associated with susceptibility and resistance to insulin-dependent diabetes mellitus (IDDM), and the role of DQ molecule in IDDM has been suggested. To further clarify the association of DQ alleles with IDDM, we determined the nucleotide sequences of full-length cDNA from 13 DQA1 alleles and 14 DQB1 alleles. The sequencing analysis revealed sequence polymorphisms outside the hypervariable region of DQ genes. We then analyzed the DQA1 and DQB1 polymorphisms along with that of DRB genes in 86 B-lymphoblastoid cell lines (B-LCLs) from various ethnic groups and in healthy unrelated Japanese and Norwegian individuals. The allelic and haplotypic distributions in each population revealed the characteristic haplotypic formation in the HLA class II region. HLA genes in 139 Japanese and 100 Norwegian IDDM patients were analyzed. DQB1*0301 was negatively associated with IDDM in both ethnic groups, irrespective of associated DRB1 and DQA1 alleles. In DQB1*0302 positive populations, which represented a positive association with IDDM in both ethnic groups, DRB1*0401, *0404, *0802 haplotypes increased in the patients, whereas DRB1*0406 haplotype decreased. Considering about the hierarchy in DRB1 alleles with IDDM susceptibility (DRB1*0401>*0404>*0403 in Norwegian and DRB1*0802>*0403>*0406 in Japanese), the genetic predisposition to IDDM is suggested to be defined by the combination of DR-associated susceptibility and DQ-associated susceptibility and by the DQ-associated resistance which is a dominant genetic trait.